Stop raiding music gigs, please - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
LIVE music – or gigging to us troubadours – is probably the most misunderstood activity. I use “activity” because I want to be inclusive: not everyone who gigs is a full-time musician.